Radiation-direction steerable nanoantennae - Bibbò, Luigi; Liu, Qiang; Khan, Karim; Yadav, Ashish; Elshahat, Sayed; Abood, Israa; Ouyang, Zhengbiao (SN applied sciences, 2019)
In this work, we design a novel reflection nanoantenna with a metasurface containing an array of silver nanoparticles. Moreover, an electro-optical (EO) layer is introduced to produce radiation-direction steerability. Finite-element simulations are conducted to verify the optical responses through radiation pattern, directivity, and gain of the proposed structure, showing a good tunable directional nanoantenna with a single control voltage applied on a thin EO layer, without requiring complicated rotating structures or hundreds of phase-shifting units. The joint action of the plasmon surface waves and the EO layer in the nanoantennae leads to the voltage-angle steerability for its radiation directions. The nanoantennae can find applications in biologic sensors, microscopy, spectroscopy, energy transfer, wireless connection in and among chips, light extraction from single photon source and subwavelength sized lasers, micro radar systems for micro- robots or submarines used inside human body for navigation in the veins or arteries, and compensation of fabrication errors.